2015
DOI: 10.5897/ajar2014.9046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application rates of Calcium and Boron on yield and yield attributes of soybean (Glycine max)

Abstract: Foliar fertilizers of soybeans have been widely reported in many field trials. Although Calcium and Boron are essential nutrients for soybean, research results have shown that foliar application of nutrients has been contradictory. The objective of this study was to evaluate the soybean response by applying different foliar fertilizer rates Calcium and Boron on yield components and soybean yield applied at flowering (stadia fenologic R3). Two experiments were carried out during two successive seasons 2009-2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This favored more vegetative growth and produced more dry matter accumulations in soybean plants, thus increasing the pod length of soybean. A similar result was observed by Peer et al (2013), who reported that all the weed control treatments significantly influenced the yieldcontributing characteristics of soybeans, including pod length.…”
Section: Pod Length (Cm)supporting
confidence: 87%
See 1 more Smart Citation
“…This favored more vegetative growth and produced more dry matter accumulations in soybean plants, thus increasing the pod length of soybean. A similar result was observed by Peer et al (2013), who reported that all the weed control treatments significantly influenced the yieldcontributing characteristics of soybeans, including pod length.…”
Section: Pod Length (Cm)supporting
confidence: 87%
“…Jadhav et al (2013) reported that in weed management treatments, i.e., quizalofopethyl 0.05 kg ha -1 and chlorimuronethyl 0.009 kg ha -1 as post-emergence at 15 DAS + hand weeding at 30 DAS, recorded significantly had higher seeds pod -1 which was at par with the weed-free check. Peer et al (2013) reported that integrated use of herbicides and cultural management gave better seed yield and yield attributed than their sole application.…”
Section: Number Of Seeds Pod -1mentioning
confidence: 99%
“…Doğan et al (2013) found that boron application under drought stress increased the amount of chlorophyll and proline but did not significantly change the amount of MDA. Also, some studies indicated that the application of boron 30 days after germination had no effect on yield (Seidel et al, 2015).…”
Section: Boron Dose-yield Relationshipsmentioning
confidence: 99%
“…Lacerda et al (2017) attributed the unresponsiveness of the soybean crop to B fertilization reported by Calonego et al (2010) to high soil B availability; contents were 0.43 mg dm -3 at the study site. Other authors have also associated soybean unresponsiveness with B foliar application to its low efficiency (Seidel et al, 2015;Bruns, 2017;Nakao et al, 2018;Santos et al, 2019;Ratke et al, 2020). Response curves between applied B rates, leaf B contents, and plot yield.…”
Section: Resultsmentioning
confidence: 99%